Pengolahan Buah Aren Menjadi Produk Kolang-Kaling di Desa Kopi Kecamatan Bulango Utara Kabupaten Bone Bolango - Rezqiwati Ishak; Amiruddin Amiruddin; Swastiani Dunggio; Syahrir Abdussamad (ELDIMAS: Jurnal Pengabdian Pada Masyarakat, 2023)
The aren tree is a type of palm that has high economic value and is widely distributed in Indonesia, especially in Bone Bolango Regency, Gorontalo Province. All parts of the palm tree from the leaves to the roots can be used. The superior products of aren as a source of food and energy include brown sugar, ant sugar, fresh sap, and fruit and are used for various handicraft products and building materials. The purpose of implementing PKM in the coffee village is to take advantage of the village's potential to develop the community's economy by making processed palm fruit into processed fruit and fro. The method used in this is assisting MSMEs so that they can develop according to technological developments. The results achieved in this PKM are processed palm fruit products in the form of fro which are already in packaging so that they can support the validity period or expiration date of processed palm fruit products.